The influence of some dietary components on intestinal microbiota - Abruzzo, Alida; Damiano, Giuseppe; Altomare, Roberta; Palumbo, Vincenzo Davide; Tomasello, Giovanni; Buscemi, Salvatore; Lo Monte, Giulia; Maione, Carolina; Buscemi, Giuseppe; Lo Monte, Attilio Ignazio (Progress in Nutrition, 2016)
The gut microbiota is the set of symbiotic microorganisms that resides in our intestine. The interaction between the gut microbiota and the mucosal immune system can be altered as a result of shifts in the composition or metabolic activity of the intestinal microflora. Recent studies establish that diet is one of the main involved factors in determining the microbial composition of the gut suggesting its role as external factor able to promote the onset of specific diseases by disrupting the immune homeostasis. Starting from the evidence that the 57% of the gut microbiota’s entire variation are due to dietary alterations this review aims at providing an overview of the positive impact of some dietary components on gut microbiota composition.